Can Er:YAG laser be an alternative to conventional methods for repairing composite resins? - Digdem Eren; Özden Bektaş; Şeyda Siso (Cumhuriyet University, 2013)
Abstract Objective: The aim of this study was to compare the effect of four different surface treatments on the repair bond strength of aged composite resin by employing the micro-shear test. Materials and Method: Forty-eight composite blocks were prepared. All samples were thermocycled for 1000 cycles between (5±2) and (55±2) ◦C with a dwell time of 30 s and a transfer time of 5 s. The samples were randomly divided into four groups and were subjected to the following treatments (n=12): Group 1 - phosphoric acid; Group 2 - diamond bur ; Group 3 - diamond bur+ phosphoric acid; Group 4 - Er:YAG Laser. After the aging procedure, fresh microhybrid resin composite was bonded to the treated surfaces with an etch and rinse adhesive resin. The repair bond strength of each sample was determined using a micro-shear bond strength test. All data were analyzed using the Kruskal Wallis test. Results: There were no significant differences among samples in the four groups. Conclusion: Based on the results of this study, each of the four surface treatment methods produced sufficient repair bond strength. Clinical Relevance: A proper bonding must be created between the existing aged composite and the new one for successful repair. Key Words: Repair bond strength, composite resin, Er:YAG laser, micro-shear